PUBLIC PERCEPTION OF THE SPREAD OF THE COVID-19 VIRUS AND VACCINATION ACTIVITIES - Syafira, Aulia; Putri, Lili Dasa (Universitas Nusa Cendana, 2023)
Covid-19 is a type of virus that is currently on the rise, and its spread throughout the world is increasing; the spread of this virus is quite fast because almost everyone in the world has been infected; As a result, all governments around the world are working hand in hand to eradicate and inhibit the growth of this covid-19, and take steps to reduce it, one of which is the provision of a covid-19 vaccine. The Covid-19 vaccine is one form of effort made by governments around the world to combat the current case of the spread of Covid-19, where the proliferation of Covid-19 cases which are increasingly mushrooming has made it difficult for all parties, especially the government, to restore order. This material is collected through library research operations from various related journals/articles, to ensure that the contents are relevant to the themes discussed.